The Juridical Review of the Consequences of Online & Offline Promotion of Notary Position Conducted by A Notary based on The Notary's Ethics Code - Abimanyu Muhammad Farhan B.; Ery Agus Priyono (Universitas Islam Sultan Agung, 2023)
. This study aims to determine the consequences borne by notaries on notaries who promote positions online and offline based on the notary's code of ethics. The research method used is a normative juridical approach, (library research), which is a research approach that uses the main law, as well as reviewing several theoretical matters related to legal principles, legal doctrines, regulations and legal systems related to research What is being discussed using secondary data includes principles, rules, norms, and legal rules contained in laws and regulations and other regulations. The result of this study is that violations of the code of ethics committed by notaries will provide consequences regulated in the notary code of ethics in the form of reprimands, warnings, temporary dismissals, respectful dismissals, and disrespectful dismissals decided by the Notary Honor Council established by the Indonesian Notary Association (INI).